Interrogative suggestibility, self-esteem, and the influence of negative life-events - Drake, Kim E. (Legal and criminological psychology, 2008)
Purpose. Past research has frequently demonstrated the impact of life adversity on the behaviour and mindset of individuals. In terms of the formal police interview, the experience of negative life-events may have an effect upon interviewee performance. This study, therefore, aims to investigate how negative life-events may influence interviewee performance on the Gudjonsson suggestibility scale (GSS). Moreover, self-esteem will also be investigated in relation to both the experience of negative life-events and interrogative suggestibility. Method. Sixty participants were administered the GSS1. In between the immediate and delayed recall phases, interviewees were asked to complete the culture-free self-esteem inventory, the life-events questionnaire and the Eysenck personality questionnaire. Results. Negative life-events (NLEs) were significantly correlated with all of the GSS suggestibility scores (yield 1, yield 2, shift and total Suggestibility). Contrary to past research, however, self-esteem scores were not significantly related to any of the GSS components or to NLE scores. Conclusion. This paper is the first to show a link between the experience of NLEs and GSS scores. The findings suggest that interviewees reporting a high number of NLEs are significantly more susceptible to the leading questions, as well as to negative feedback, administered during the GSS interview. Erroneous reports and false confessions may thus be more likely with such interviewees, potentially classifying them as vulnerable witnesses.